ABERRANT LEFT TESTICULAR ARTERY ALONGWITH THREE LEFT RENAL ARTERIES - Alamgir, Afzal; Bangash, Assad (Journal of Ayub Medical College Abbottabad, 1991)
A male cadaver of a middle-aged was dissected in the Department of Anatomy of Ayub Medical College, Abbottabad. The cadaver was of a well-built person victim of a road traffic accident, and he had no gross anomaly elsewhere in the body as revealed by dissection of various regions. But after opening of abdominal cavity and reflection of peritoneum from the posterior abdominal wall three renal arteries of varying size were found on the left side separately originating from abdominal aorta alongwith two renal veins draining as a single vein in the inferior vena cava. The left testicular artery was arising from one of the three renal arteries which was of the largest caliber. The left testicular vein was found to be draining into the left renal vein. On the right side, only a single renal artery and a vein were fond and the right testicular artery was arising from the aorta just below the origin of right renal artery. The right testicular vein was draining into the inferior vena cava. Bothe the kidneys were of the normal size.